POLIGAMI RAMAH PEREMPUAN; CATATAN KRITIS ATAS POLIGAMI KUANTITATIF- KUALITATIF PERSPEKTIF MUHAMMAD SYAHRÛR - A, Syamsuri (Universitas Islam Negeri Mataram, 2017)
Polygamy has become a controversial topic in the discoursesof gender relations, including in Islam. It is therefore always attractive toscholars and experts to discuss this topic. Muslims thinkers have attemptedto re-interpret polygamy either to reject it, fasten its procedure or to allowit under certain conditions. One leading contemporary Muslim scholar whois concerned with the issues of gender relations and polygamy under Islamis Muhammad Shahrur. This article examines Shahrur’s view on polygamy.Based on his several works as the main data, this study analyzes his approachto polygamy and criticizes it. He is well-known for the theory of limit. Heemploys a qualitative-quantitative concept to formulate an understandingof polygamy which is just for women, as this is often neglected under thestipulation of normative Islamic law. However, as a system of thought,Syahrur’s idea on polygamy opens up criticism despite its novelty idea that isless severe to women since he limits polygamy. Dalam relasi gender, poligami menjadi isu yang sensitif tetapi seksiuntuk dikaji. Sejumlah pemikir Islam ikut terlibat dalam upaya menempatkanpoligami yang ramah perempuan. Muhamaad Syahrur sebagai salah satu daripara pemikir Islam tersebut melibatkan diri dalam kajian poligami. Denganmetode limitasi dan pendekatan linguistik, Syahrur memformulasikanpoligami kuantitatif-kualitatif sebagai ikhtiarnya menemukan poligami yangberkeadilan dan ramah perempuan. Sebagai sebuah pemikiran, kesimpulanSyahrur tentang poligami menyisakan celah untuk dikritisi. Kritik dalam tulisanini terutama mengenai konsistensiSyahrurdalam membangun teori poligamikuantitatif- kualitatif.